Nitrogen recovery from anaerobic digestate via ammonia stripping and absorbing with a nitrified solution. Issue 3 (June 2022) - Alhelal, Ismail I.; Loetscher, Lucas H.; Sharvelle, Sybil; Reardon, Kenneth F.
Abstract: Anaerobic digesters produce renewable energy from organic wastes, including animal wastes. However, ammonia toxicity stemming from the nitrogen content of animal wastes reduces the feasibility of the process. Approaches for stripping ammonia and recovering it via the use of strong mineral acids have disadvantages. Here, we evaluate a process that includes ammonia removal coupled with a novel nitrogen recovery strategy using a solution from biological nitrification. This approach has the potential to reduce ammonia toxicity while providing valuable biofertilizer from nitrification. Since this integrated process couples sub-systems that have different operating conditions, an experimental laboratory-scale study and Aspen Plus model of the nitrogen removal and recovery system (consisting of stripping and absorption units) were used to assess process performance as a function of stripping unit temperature and feed pH, as well as of the absorption unit feed pH and nitrogen concentrations. Based on results of the experiments and modeling, the recommended conditions for the integrated stripper-absorber system were a feed pH of 10 and operating temperature of 50 °C for the stripping unit, and a feed pH of 7 and feed nitrogen concentrations of 7 g-N/L for the absorption unit. While the feed pH and temperature had a large impact on ammonia stripping, neither the feed pH nor the nitrogen concentration in the feed led to a significant difference in the ammonia absorption. These results support the use of this new approach of using nitrified solution as the ammonia absorbent in an integrated anaerobic digestion process. Graphical Abstract: ga1 Highlights: The process evaluated in this work reduces ammonia toxicity in anaerobic digestion while providing fertilizer. The use of nitrification solution to recover nitrogen eliminates the use of mineral acids. Operational conditions for nitrogen removal and recovery were determined.